Structural and functional characterization of an Isd‐type haem‐degradation enzyme from Listeria monocytogenes. (1st March 2014) - Duong, Thao; Park, Kwangsu; Kim, Truc; Kang, Sung Wook; Hahn, Myung Joon; Hwang, Hye‐Yeon; Kim, Kyeong Kyu
<x xml:space="preserve">Abstract</x> Bacterial pathogens have evolved diverse types of efficient machinery to acquire haem, the most abundant source of iron in the human body, and degrade it for the utilization of iron. Gram‐positive bacteria commonly encode IsdG‐family proteins as haem‐degrading monooxygenases. Listeria monocytogenes is predicted to possess an IsdG‐type protein (Lmo2213), but the residues involved in haem monooxygenase activity are not well conserved and there is an extra N‐terminal domain in Lmo2213. Therefore, its function and mechanism of action cannot be predicted. In this study, the crystal structure of Lmo2213 was determined at 1.75 Å resolution and its haem‐binding and haem‐degradation activities were confirmed. Structure‐based mutational and functional assays of this protein, designated as an Isd‐type L. monocytogenes haem‐degrading enzyme (Isd‐LmHde), identified that Glu71, Tyr87 and Trp129 play important roles in haem degradation and that the N‐terminal domain is also critical for its haem‐degrading activity. The haem‐degradation product of Isd‐LmHde is verified to be biliverdin, which is also known to be the degradation product of other bacterial haem oxygenases. This study, the first structural and functional report of the haem‐degradation system in L. monocytogenes, sheds light on the concealed haem‐utilization system in this life‐threatening human pathogen.